A comparative study of postoperative complications in emergency versus elective laparotomy at a tertiary care centre - S., Chauhan; B., Chauhan; H., Sharma (International Surgery Journal, 2017)
Background: The incidences of post-operative complications are higher after laparotomy particularly in emergency. This study was aimed to evaluate and compare postoperative complications after emergency versus elective laparotomy performed at Bundelkhand Medical College, Sagar. Methods: This comparative study was carried out at Department of General Surgery in Bundelkhand Medical College, Sagar, Madhya Pradesh during period of January 2015 to February 2016. All the patients who underwent laparotomy (elective or emergency) were included in the study. Demographic data about patients was collected and noted in pro forma. Patients were followed in postoperative period and any complication developed recorded. Complications compared according to nature of laparotomy whether elective or emergency. Results: A total of 350 patients underwent emergency laparotomy and 50 patients underwent elective laparotomy. 128 (36.57%) patients developed complications following emergency laparotomy while 11 (22%) patients developed complication after elective laparotomy. Postoperative complications following emergency laparotomy included pyrexia (18.2%) followed by nausea and vomiting (12%), wound infection (11.4%), respiratory tract infection (6.85%), urinary tract infection (2.28%), gastrointestinal complications (3.71%), toxemia and septicaemia (8%). After elective laparotomy 20% patients showed postoperative fever, 10% patients suffered from postoperative nausea and vomiting and wound infection was noted in 4% patients. Conclusions: In comparison to elective laparotomy postoperative complications are more common in emergency laparotomy.